The invention of the helium-neon gas laser by Ali Javan - Larbani, Moussa; Ismail, Ahmad Faris (IIUM Press, 2011)
The chief aim of this chapter is to highlight one ofthe most important inventions ofthe 20th , century which was created by the Iranian professor Ali lavan. This invention is the gas laser composed of Helium-Neon Laser. In this chapter the theory of the gas laser, its main components and advantages will be dealt with in comparison to the normal laser. The significance of the study lies in the fact that Ali Javan was one of the main inventors or more precisely a co-inventor of the gas laser. He has yet the distinction, however, for his principal contributions in the period preceding the laser, this period itself having its beginning with the original discovery of the well-known masers, the equivalent of the lasers operating at the microwave frequencies (A. lavan, 1961). As events had it in lavan own history, and shortly following within month's time ofthis original discovery